(untitled) (Ascendens Asia Singapore – Bestlink College of the Philippines Journal of Multidisciplinary Research, 2024)
This research study aims to determine whether social media marketing trends affect customers’ interests. In addition, this paper uses existing findings to identify factors that may affect customer’s interest. Customer’s interests will be affected by different types of social media marketing trends. Maintaining a strong customer relationship will be a great advantage for the business. Thus, it will benefit the said business and make it more profitable. The study utilized a quantitative research method and purposive sampling where the researchers focused on fifty (50) customers of iStan K-Pop Merch and created five (4) parts to the survey questionnaire based on the problem of the studies, separating each problem accordingly. The researcher uses frequency and percentage to determine the respondents and description according to age, occupation, and family income and used weighted mean to define the response of customers in terms of price, product, performance, promotion, and the effects of social media marketing trends on customer’s behaviour of iStan K-Pop Merch in terms of advertisement, sales and promotion, event marketing, video content, and influencer. From the findings, after the researchers conducted an online survey questionnaire on customer interest and purchasing behaviour of iStan K-Pop Merch in terms of age, occupation, family income, price, product, performance, promotion, advertisement, sales and promotion, event marketing, video content, and influencer as "Very Strongly Effect"; And the problems encountered by the customer of iStan K-Pop Merch is the quality of other merchandise is not good. This analysis contributes to this discussion by examining the effects of social media marketing trends on customers’ interest in iStan K-Pop Merch.